How do plants achieve tolerance to phosphorus deficiency? Small causes with big effects - Wissuwa, Matthias (Oxford University Press, 2003)
Genotypic differences in phosphorus (P) uptake from P-deficient soils may be due to higher root growth or higher external root efficiency (micrograms of P taken up per square centimeter of root surface area). Both factors are highly interrelated because any additional P provided by externally efficient roots will also stimulate root growth. It will be necessary to separate both factors to identify a primary mechanism to formulate hypotheses on pathways and genes causing genotypic differences in P uptake. For this purpose, a plant growth model was developed for rice (Oryza sativa) grown under highly P-deficient conditions. Model simulations showed that small changes in root growth-related parameters had big effects on P uptake. Increasing root fineness or the internal efficiency for root dry matter production (dry matter accumulated per unit P distributed to roots) by 22% was sufficient to increase P uptake by a factor of three. That same effect could be achieved by a 33% increase in external root efficiency. However, the direct effect of increasing external root efficiency accounted for little over 10% of the 3-fold increase in P uptake. The remaining 90% was due to enhanced root growth as a result of higher P uptake per unit root size. These results demonstrate that large genotypic differences in P uptake from a P-deficient soil can be caused by rather small changes in tolerance mechanisms. Such changes will be particularly difficult to detect for external efficiency because they are likely overshadowed by secondary root growth effects.